As a matter of convenience? / Norhidayah Ali, Zuraidah Mohamed Isa and Dahlia Ibrahim - Ali, Norhidayah; Mohamed Isa, Zuraidah; Ibrahim, Dahlia (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Nowadays, due to time and location constraint factors, consumers are looking for faster, more efficient and more convenient services. Consumer convenience has always been associated to saving time and effort in getting all necessary information, products and services, preferably all in one go. Consumers are looking for more efficient ways to perform their daily routines and therefore, convenience has become an essential consideration. In offering convenient services to the consumers, most companies whether in the product or service industries are riding on online technology to provide instant and round-the-clock accessibility and ease. Online technology provides convenience in terms of much easier and faster access to information, entertainment, networking as well as purchasing. Some examples of online service and product providers are the banking, food & beverages (F&B), apparel, cosmetic and book industries.